2009
DOI: 10.1345/aph.1m347
|View full text |Cite
|
Sign up to set email alerts
|

Lofexidine, an α2-Receptor Agonist for Opioid Detoxification

Abstract: Lofexidine appears to be a promising agent for opioid detoxification. If approved, it would be the first nonopioid agent approved for this indication. Further large-scale controlled studies are needed to identify the safest, most effective dosage regimen required to achieve opioid detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 22 publications
0
37
0
5
Order By: Relevance
“…Эти препараты стимулируют пресинапти ческие ADRA2A рецепторы, снижают выделение норадреналина (НА) в синаптическую щель и ши роко применяются для купирования симптомов ост рого ОАС [35]. Предполагается, что этот эффект также можно использовать и в постабстинентном периоде [16], в частности, с целью повышения ус тойчивости к стрессорным воздействиям как важ ным причинам срыва. В исследовании R. Sinha et al [33] было показано, что комбинация перораль ного налтрексона и лофексидина способствует луч шему удержанию в программе терапии без реци дива (4 недели), а также снижению влечения к опи атам по сравнению с группой плацебо.…”
Section: комбинированная терапияunclassified
“…Эти препараты стимулируют пресинапти ческие ADRA2A рецепторы, снижают выделение норадреналина (НА) в синаптическую щель и ши роко применяются для купирования симптомов ост рого ОАС [35]. Предполагается, что этот эффект также можно использовать и в постабстинентном периоде [16], в частности, с целью повышения ус тойчивости к стрессорным воздействиям как важ ным причинам срыва. В исследовании R. Sinha et al [33] было показано, что комбинация перораль ного налтрексона и лофексидина способствует луч шему удержанию в программе терапии без реци дива (4 недели), а также снижению влечения к опи атам по сравнению с группой плацебо.…”
Section: комбинированная терапияunclassified
“…In recent years, lofexidine has been studied as a possible alternative to clonidine to treat opioid withdrawal (for a review see Gish et al 2010). Lofexidine is an alpha-2-adrenoreceptor agonist that is structurally related to clonidine but is not active as a hypertensive agent.…”
Section: (Evidence Level E)mentioning
confidence: 99%
“…Preliminary studies have shown that lofexidine has a better safety profile than clonidine, with fewer hypotensive effects. Studies have shown that lofexidine is effective in calming adrenergic withdrawal symptoms [43,44]. It does not, however, calm insomnia or myalgia which are frequent.…”
Section: Opiate Withdrawal Treatmentmentioning
confidence: 99%